2006
DOI: 10.1021/jo060920l
|View full text |Cite
|
Sign up to set email alerts
|

Carbocyclic Ribosylamines:  Synthesis of 5-Substituted Carbocyclic β-Ribofuranosylamines

Abstract: A synthesis of 5-substituted cyclopentylamine precursors for 5'-substituted carbocyclic nucleoside analogues was developed. We show that the stereochemistry of the OsO4-catalyzed hydroxylation of an apically brominated lactam, 7-bromo-2-azabicyclo[2.2.1]hept-5-en-3-one, can be controlled through the appropriate selection of the lactam N-H protecting group. Sterically large groups direct the hydroxylation to the exo-face of the olefin, yielding hydroxylation products that can be converted into analogues of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The resolution of the (±)-γ-lactam 4 was carried out with savinase in 50% THF–phosphate buffer solution (pH 8.0) for 2 days, selectively producing only the optically pure γ-lactam (−)- 4 in 84% yield with an enantiomeric excess (ee) of more than 99%. It has been reported that the stereochemistry of OsO 4 -catalyzed hydroxylation of (−)-2-azabicyclo[2.2.1]hept-5-en-3-one (γ-lactam 3 ) can be controlled through the N–H protecting group of the lactam. , A large group sterically directs the hydroxylation to the exo face of an olefin, yielding a hydroxylation product that can be converted into an analogue of carbocyclic riboside, as the exo isomer was desired for our synthesis. Thus, a bulkier Boc protecting group would prevent the OsO 4 oxidation from the β-face of the olefin and favor the production of the α-diol.…”
Section: Resultsmentioning
confidence: 99%
“…The resolution of the (±)-γ-lactam 4 was carried out with savinase in 50% THF–phosphate buffer solution (pH 8.0) for 2 days, selectively producing only the optically pure γ-lactam (−)- 4 in 84% yield with an enantiomeric excess (ee) of more than 99%. It has been reported that the stereochemistry of OsO 4 -catalyzed hydroxylation of (−)-2-azabicyclo[2.2.1]hept-5-en-3-one (γ-lactam 3 ) can be controlled through the N–H protecting group of the lactam. , A large group sterically directs the hydroxylation to the exo face of an olefin, yielding a hydroxylation product that can be converted into an analogue of carbocyclic riboside, as the exo isomer was desired for our synthesis. Thus, a bulkier Boc protecting group would prevent the OsO 4 oxidation from the β-face of the olefin and favor the production of the α-diol.…”
Section: Resultsmentioning
confidence: 99%
“…Slama et al studied the effects of steric bulk at the nitrogen of the Vince lactam in the hydroxylation reaction. The goals of the study included preparation of carbocyclic β-ribofuranosylamines . Since presence of bulky groups on the nitrogen exerts a profound effect in formation of exo-hydroxylation products, the authors considered studying the stereochemical effect of the approach of hydroxylating agent from the least hindered side of N-protected Vince lactam.…”
Section: Reactivity Profile Of Vince Lactammentioning
confidence: 99%
“…The goals of the study included preparation of carbocyclic β-ribofuranosylamines. 214 Since presence of bulky groups on the nitrogen exerts a profound effect in formation of exo-hydroxylation products, the authors considered studying the stereochemical effect of the approach of hydroxylating agent from the least hindered side of Nprotected Vince lactam. OsO 4 catalyzed cis-hydroxylation validated the hypothesis.…”
Section: Hydroxylation Of Vince Lactammentioning
confidence: 99%